ANALISIS VARIASI PARAMETER PROSES PERMESINAN TERHADAP TINGKAT KEKASARAN PERMUKAAN MATERIAL SKD 11 DENGAN MENGGUNAKAN MESIN BUBUT GEMINIS - Fachrezi, Rizki; KURNIAWAN, ZALDY; ASWIN, FAJAR (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The success of the world's manufacturing industry to improve production processes is strongly influenced by the production machine tools used. Shaft is a product that requires a low surface roughness value during lathe processing, especially the Tornos Geminis S.L. semi-automatic lathe. The purpose of this study was to determine the surface roughness of carbon steel. This study uses parameters that affect the shape of the surface roughness value of the SKD11 material, namely the spindle rotation rate (1000 Rpm, 760 Rpm, 610 Rpm), feed depth level (0.4 mm, 0.6 mm, 0.8 mm)) and feeding speed. (0.8mm)/put, 0.9mm/put, 0.10mm/put). The lowest value of surface roughness of the Skd 11 material was obtained with a spindle speed of 1000 Rpm, feed rate of 0.9 mm/put and depth of cut 0.4 mm, and a surface roughness value of 1.636 m.